Security, ethnicity, nationalism. Issue 2 (6th June 2017) - Neumann, Iver B.
Abstract: Using Slavic examples, the article looks at the nationalism/security nexus present today between the birth of ethnicities (early middle ages) and the birth of nationalism (eighteenth century). I discuss how Slavic ethnicity emerged in Greek and Roman security thinking. Others were classified in terms of ethnoi and were then interpellated into this self‐understanding. If ethnicity is an identity for the Other, then nationalism is an identity for the Self. It becomes a security concern not to order the Other polity's identity, as did the Byzantines, but to see to it that groups that may threaten your own nationalism – minorities, imperial subjects – cannot embrace nationalism. The policy of denying nationhood to minorities must be understood amongst other things as security policy. The organic understanding of the nation as young and vital demonstrates a third interstice between security and nationalism. If the young and vital nation is to grow and expand at the expense of the old and tired, then the polity that represents itself as a young and vital nation is by dint of that representation alone a security threat against those that they represent as old and tired. Finally, I discuss how this theme is played out in today's Russia